Primary care providers perspective on the strengths, challenges, opportunities, and threats of the integrated disease surveillance program in Puducherry - Roy, Durgesh; Kannusamy, Sivaranjani; Parambilankandi, Akshay; Lakshmansamy, Ravivarman; Vissvesaran, Srividya; Gurusamy, Ragunathan; Thulasingam, Mahalakshmy; Sekhar Kar, Sitanshu (International Journal Of Community Medicine And Public Health, 2025)
Integrated disease surveillance program (IDSP) is a decentralized district-based system of weekly surveillance for communicable diseases. Reviewing the existing system gives valuable insight into the surveillance system as we move toward a technology-enabled integrated health information portal (IHIP). Hence, this study explored the primary care provider's perspective on the strengths, challenges, opportunities, and threats (SCOT) of various components in IDSP, Puducherry. We conducted this qualitative study following a descriptive theoretical underpinning and included in-depth interviews of selected medical officers (MO) of primary health centers (PHCs) in Puducherry district. SCOT analysis was done by interviewing eight purposively selected MO working in the PHCs. It's a manual thematic analysis. The strength perspective is regular review, monitoring, good communication, capabilities of the IDSP unit, and Outbreak response. The challenges are offline data reporting and inadequate manpower. Opportunities are Intersectoral coordination. The perspective of threats is data quality and community participation.